Oboczność ir || er (≤*ir, yr) w Księgach o gospodarstwie (Kraków 1549, Helena Unglerowi) - Osiewicz, Marek (Slavia Occidentalis, 2015)
This article presents a subsequent stage of research into the textual variability of alterations of the phonetic forms in the first Polish edition of Księgi o gospodarstwie by Piotr Krescentyn (Krakow 1549). The ir || er group has been analysed as continuants of the Proto-Slavic conjunctions *ir, yr. The status of the discussed phonetic alternation depends on the core location and the textual distribution. It has been established that within the specific cores, the status of the alternation attested in Cresc is related to the status identified in other printed texts of that time and is considerably progressive. The second part of the text (CrescII) tends to be much more normalized where the innovative forms are preferred. However, this part of the text also tends to be most diversified with respect to the analysed phonetic alternation. A differentiation of the textual distribution of the opposite forms has also revealed two new text boundaries stretching between columns 409/410 and 524/525.